PENGARUH POC LIMBAH CUCIAN BERAS TERHADAP PERTUMBUHAN DAN HASIL SAWI CAISIM (Brassica juncea L.) - Suryadi; Yuni Irfan; Dwi Fitriani; Fiana Podesta (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
This study aims to analyze the effect of Liquid Organic Fertilizer (POC) from rice washing waste on the growth of Chinese cabbage (caisim) and to determine the most optimal application dose. The study used a Randomized Block Design (RBD) with five dose levels: 0 ml (control), 150 ml, 250 ml, 350 ml, and 450 ml per plant. A total of 125 plants were observed through five replication blocks, with the focus of parameters on vegetative growth and plant biomass. Application of POC from rice washing waste significantly increased the number of leaves, leaf width, plant fresh weight, and root fresh weight, but did not have a significant effect on plant height. A dose of 250 ml/plant (P2) was identified as the most effective dose that produced the highest fresh weight, number of leaves, and leaf width. Thus, POC from rice washing at this dose has great potential as an environmentally friendly organic nutrient alternative for Chinese cabbage cultivation.